Lung ultrasonography to assess efficacy of intranasal and parenteral vaccinations for bovine respiratory disease (BRD) in dairy calves - Enrico Fiore; Giorgia Taio; Nicola Morandi; Elisa Mazzotta; Matteo Gianesella; Ortensio Bonato; Arnaldo Azzolin; Anastasia Lisuzzo (PLoS ONE, 2026)
Vaccination is used to control bovine respiratory disease (BRD). The aim of this study was to evaluate BRD vaccine efficacy through the lung lesions area in dairy calves, also discriminating the lung health status at vaccine administration. One hundred forty-nine dairy calves were enrolled and divided according to vaccine protocol and initial lung condition: healthy (H-CTR; n = 17) and diseased (D-CTR; n = 24) control group; healthy (H-INT; n = 28) and diseased (D-INT; n = 18) intranasal group, healthy (H-VAC; n = 31) and diseased (D-VAC; n = 31) intranasal and parenteral group. Intranasal vaccination was against bovine parainfluenza-3 and respiratory syncytial viruses, while parenteral vaccination was also against Mannheimia haemolytica. Animals were assessed by clinical and ultrasonographical examinations at 10, 17, 38, 52 days; ultrasonography and lung lesion scores (US and LLS), and total consolidation area (TC_A) were greater in CTR with increasing levels over time in both H-CTR (US: 1.45 at 10d vs. 3.8–4.4 thereafter; LLS: 3.5 at 10d vs. 12.4–13.3 thereafter; TC_A: 3.9 cm 2 at 10d vs. 9.8–15.4 cm 2 thereafter) and D-CTR groups (LLS: 12.1 at 10d vs. 13.0–15.7 thereafter; TC_A: 23.4 cm 2 at 10d vs. 34.9–49.4 cm 2 thereafter). However, TC_A was maintained in H-INT and reduced in D-INT (22.3 cm 2 at 10d vs. 14.3 cm 2 at 52d). The VAC had the lowest values in US, LLS and TC_A. The H-VAC preserved the initial condition for these parameters, while D-VAC showed a reduction in US (3.8 at 10d vs. 3.0 at 52d) and TC_A (18.4 cm 2 at 10d vs. 10.9 cm 2 at 52d). In conclusion, the combination of intranasal and parenteral vaccination reduced the progression of lung TC_A severity in both initially healthy and diseased female dairy calves.